Artemisia vulgaris Linn: an updated review on its multiple biological activities - Deepali Siwan; Dipali Nandave; Mukesh Nandave (SpringerOpen, 2022)
Abstract Background Artemisia vulgaris Linn, an annual herb, is also known as Mugwort or Wormwood in English, Nagadouna in Hindi, Mashibattiri, or Machipatri in Tamil. Native habitats are temperate Asia, Europe, Northern Africa and Alaska. Ethnomedicinally, it is used in traditional treatments to treat depression, epilepsy, irritability, insomnia and stress. This plant is called Herbaka in the Philippines and is used to alleviate hypertension. It is utilized as a culinary herb in western countries and is often used to flavor rice dishes and tea in Asia. Main body of the abstract Botanical description, holistic approaches, ethnomedical uses and phytochemical screening of A. vulgaris along with its various in vitro/in vivo pharmacological activities reported are the prime focus of this literature. The primary phytoconstituents and diverse pharmacology of this plant have been fully uncovered in order to learn about its previously unrecognized ethnomedicinal uses and provide scientists with new knowledge to advance their study of this plant. Short conclusion This review includes various principle phytoconstituents (hydroxybenzoic acid, rutoside, camphen, 1, 8-cineole and α-thujone) which are extensively shown biological activities such as analgesic, anti-fungal and anti-bacterial. However, further investigations are needed for identifying chemical constituents responsible for the claimed ethnomedicinal uses along with their mechanism of action. It is also anticipated here that the review will be the current understanding of Artemisia vulgaris application in complementary and alternative medicine.